The role of denitrification genes in anaerobic growth and virulence of Flavobacterium columnare - Abdelhamed, Hossam (J Appl Microbiol, 2020)
AIMS: Comparative genomics analyses indicated that the Flavobacterium columnare genome has unique denitrification genes relative to Flavobacterium psychrophilum and Flavobacterium johnsoniae, including nasA (nitrate reductase), nirS (nitrite reductase), norB (nitric oxide reductase), and nosZ (nitrous oxide reductase). The current study determines the roles of nasA, nirS, norB, and nosZ in anaerobic growth, nitrate reduction, biofilm formation, and virulence. METHODS AND RESULTS: Four in-frame deletion mutants in virulent F. columnare strain 94–081 were constructed by allelic exchange using pCP29 plasmid. Compared with parent strain 94–081, FcΔnasA, FcΔnirS, and FcΔnosZ mutants did not grow as well anaerobically, whereas the growth of FcΔnorB strain was similar to the parent strain (FcWT). Exogenous nitrate was not significantly consumed under anaerobic conditions in FcΔnasA, FcΔnirS, and FcΔnosZ compared to parent strain 94–081. Under anaerobic conditions, FcΔnasA, FcΔnorB, and FcΔnosZ formed significantly less biofilm than the wild type strain at 24 and 96 hours, but FcΔnirS was not significantly affected. The nitrite reductase mutant FcΔnirS was highly attenuated in catfish, whereas FcΔnasA, FcΔnorB, and FcΔnosZ had similar virulence to FcWT. CONCLUSIONS: These results show, for the first time, that denitrification genes enable F. columnare to grow anaerobically using nitrate as an electron acceptor, and nitrite reductase contributes to F. columnare virulence. SIGNIFICANCE AND IMPACT OF THE STUDY: These findings indicate potential for F. columnare to grow in nitrate-rich anaerobic zones in catfish production ponds, and they suggest that a FcΔnirS strain could be useful as a safe live vaccine if it protects catfish against columnaris disease.